What is the solution of the system defined by y = -x + 5 and 5x + 2y = 14?Ax=1/3, y=11/7
Bx=4/3, y=11/3
Cx=5/11,y=0
Dx=4/3,y=1

Answers

Answer 1
Answer: y = -x + 5
5x + 2y = 14

5x + 2(-x+5) = 14
5x - 2x + 10 = 14
3x = 14 - 10
3x = 4
x = 4/3 or 1 1/3

y = -x + 5
y = -4/3 + 5
y = -4/3 + (5 * 3/3)
y = -4/3 + 15/3
y = -4+15 / 3 
y = 11/3 or 3 2/3

Correct answer is B. x = 4/3 ; y = 11/3


Answer 2
Answer:

Answer:

the answer is c i think


Related Questions

5 cm 13 cm and 12 cm is a right triangle
A right triangle has an hypotenuse of 155 centimeters and a leg of 124 centimeters. Which of these is the length of the other leg ?A. 93 cm B. 97 cm C.103 cm D. 107 cm
In the broken wagon wheel CD=48 OY, the perpendicular bisector of CD=7. what is the diameter of the wagon wheel
Last month, Rhonda earned $3200. Of that amount, she spent $1350 on rent. What percent of her income went to rent, to the nearest tenth of a percent?
The pattern 0, 15, 30, 45, ________, follows the "add 15" rule. Use words to describe the rule and write the next term.pls writ abt 1-2 sentences asap :(((

Multiply the following vertically(3x+2y+1) (2x-3y-5)

Answers

Answer:

To multiply the expressions (3x + 2y + 1) and (2x - 3y - 5) vertically, we will use the distributive property and multiply each term from the first expression with each term from the second expression.

Starting with the first term in the first expression, which is 3x, we multiply it with each term in the second expression:

(3x) * (2x) = 6x^2

(3x) * (-3y) = -9xy

(3x) * (-5) = -15x

Next, we move to the second term in the first expression, which is 2y:

(2y) * (2x) = 4xy

(2y) * (-3y) = -6y^2

(2y) * (-5) = -10y

Finally, we multiply the last term in the first expression, which is 1, with each term in the second expression:

(1) * (2x) = 2x

(1) * (-3y) = -3y

(1) * (-5) = -5

Now, let's add up all the results:

6x^2 - 9xy - 15x + 4xy - 6y^2 - 10y + 2x - 3y - 5

Simplifying this expression further, we have:

6x^2 - 5x - 6y^2 - 7xy - 13y - 5

Answer:

To multiply the expressions (3x+2y+1) and (2x-3y-5) vertically, you can use the distributive property and follow these steps:

1. Start by multiplying the first term in the first expression, 3x, by each term in the second expression:

- (3x) * (2x) = 6x^2

- (3x) * (-3y) = -9xy

- (3x) * (-5) = -15x

2. Move on to the second term in the first expression, 2y:

- (2y) * (2x) = 4xy

- (2y) * (-3y) = -6y^2

- (2y) * (-5) = -10y

3. Finally, multiply the last term in the first expression, 1, by each term in the second expression:

- (1) * (2x) = 2x

- (1) * (-3y) = -3y

- (1) * (-5) = -5

Now, let's combine the like terms:

6x^2 + (-9xy) + (-15x) + 4xy + (-6y^2) + (-10y) + 2x + (-3y) + (-5)

Simplifying this expression further, we have:

6x^2 - 5x - 9xy + 4xy - 6y^2 - 10y + 2x - 3y - 5

Therefore, the result of multiplying (3x+2y+1) and (2x-3y-5) vertically is 6x^2 - 5x - 9xy + 4xy - 6y^2 - 10y + 2x - 3y - 5.

Step-by-step explanation:

Ann is buying a house that costs $250,000. She is making a down payment of 15 percent, and her closing costs will amount to 3 percent. Over the life of her loan, she will pay $282,089.89 in monthly payments. What is the total cost of her house?

Answers

BEFORE YOU PUT YOUR BLIND TRUST IN THIS ANSWER: I am not completely sure as to how house payments work, so I could be wrong about how I am calculating this...

15%= $37,500
3%= $7,500
monthly payments= $282,089.89
Original purchase price: $250,000

     250,000.00
-      37,500.00
+       7,500.00
+   282,089.89
---------------------
$   502,089.89




(that answer seems a little high to me but like I said I don't know much about house payments)

Answer:

Step-by-step explanation:

Solve 2√3+3√7 adding fraction

Answers

2√3=3.46
3
√7= 7.95

add them together equals 11.41

hope this helped!!!

Simplify Expression
3/5b - 2 + 7b - 12 - 2/5b + 14

Answers

Answer:

The answer is 7 1/5 b

Step-by-step explanation:

What is the sum of the finite arithmetic series?4+8+12+16+...+76

a. 760
b. 780
c. 800
d. 860

Answers

The answer is A. I think. Hope this helped :)

The answer is:

a. 760

The height of an object after it is released can be modeled by the function f (x) = negative 16 t squared v t s, where t is the number of seconds after the object is released, v is the upward speed in feet per second at release, and s is the starting height in feet. if a quarterback throws a ball from his hand 6 feet in the air at an upward speed of 25 feet per second, how much time does his teammate have to catch the ball?

Answers

The amount of time his teammate have to catch the ball is equal to 1.774 seconds.

Given the following function:

  • f(x) = -16t² + vt + s.
  • Displacement, s = 6ft.
  • Velocity, v = 25 ft/s.

How to calculate the amount of time?

In order to determine the amount of time his teammate have to catch the ball, we would evaluate the given position-time function as follows:

f(t) = -16t² + 25t + 6.

In Mathematics, the standard form of a quadratic equation is given by;

ax² + bx + c =0

Where:

a = -16.

b = 25.

c = 6.

Solving the function by using the quadratic formula, we have:

t = [-b ± √(b² - 4ac)]/2a

t = [-25 ± √[(25² - 4(-16)(6))]/2(-16)

t = [25/32 ± (-1/32)√1009]

t = 25/32 ± (-0.993)

t = 0.781 ± 0.993

t = 0.781 + 0.993

Time, t = 1.774 seconds.

Note: We ignored the negative value because time cannot be negative.

Read more on quadratic equation here: brainly.com/question/1214333

Answer:

B

Step-by-step explanation:

The verified dude saisd so